DESKRIPSI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PELAJARAN IPS DI KELAS TINGGI - Mutmainnah; Yunika Afryaningsih; Elvani Hartati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model in Social Studies (IPS) learning at the upper elementary school level. The background of this research stems from the fact that students’ learning outcomes in Social Studies remain relatively low, while their interest in the subject is also lacking. This condition is inseparable from the traditional teaching patterns that are still dominated by lecture-based methods. The research employed a qualitative descriptive approach through a literature study by reviewing 30 articles, consisting of 10 classroom action research studies, 10 experimental studies, and 10 development studies. The analysis focused on the application of the seven main components of CTL, namely constructivism, inquiry, questioning, learning community, modelling, reflection, and authentic assessment. The results of the review revealed variations in the implementation of CTL among the analyzed articles. Out of the 30 articles, only six consistently applied all seven CTL components. Most articles emphasized the authentic assessment component and provided less discussion on aspects such as reflection. Nevertheless, the constructivism component remains the core element that supports the achievement of CTL objectives. The findings affirm that CTL is relevant for improving Social Studies learning as it promotes students’ active participation and connects learning materials with real-life experiences.